A study on Malaysia as an Islamic state: from the religious, legal and political perspectives / Mohamad Faizul Mohd Ruslan, Saiful Sayoti and Siti Zaharah Abdullah - Mohd Ruslan, Mohamad Faizul; Sayoti, Saiful; Abdullah, Siti Zaharah (2007)
It is unknown whether Malaysia is an Islamic state or a secular country. This study is paid on how the Islamic state should be viewed. By doing the research, three perspectives had been analysed and critically viewed. The three perspectives mentioned were religious, political and legal. From the view of religious, 4 schools of thought and modern scholars' emphasis more on how Al-Quran as the sources of law and how Prophet Muhammad administered Medina as an Islamic state. From the political perspective, each party in Malaysia view Islamic state from their ideology of the parties. While from the legal perspective state that our legal system not much concentrate on the Syariah matters and the position of Islam in the Federal Constitution seems unclear and vague. Therefore, this research will be very helpful in order to understanding whether Malaysia is an Islamic state or not.